Diversity Bird in Brackish Marsh Muara Tapus Subdistrict Manduamas District Center of Tapanuli Province North Sumatera - Anisa Zuhalmi; Puji Prastowo (JBIO: jurnal biosains (the journal of biosciences), 2015)
The purposeof this research  is to knowdiversity, abundance, dominance and  distribution pattern of  bird in brackish marsh Muara Tapus Subdistrict Manduamas District Center of Tapanuli. This research was done from February 2015 until April2015. Determination of the station is based on the environmental condition. Total of place observation is 5 places. Every place consist of 4 point with distance 50 m of point accompany. Sampling by concentration point method that is to observe and to take the picture of bird which in every point observation with distance 25 metre for 30 minutes. Time of take sample from 07.00 am – 10.00 am and 04.00 pm – 06.00 pm. The result of this research, found there was 6 orders, 6 family and 8 spesies of birds. Diversity of birds was 0.879, and belonging to the low diversity. The highest abundance of birds was Dendrocygna javanica as many as 110 individual. Average of dominance was 0.512 and belonging to the dominance is moderate. The distribution pattern of birds found in the category of the cluster to 8 species.   Keywords: diversity, bird, brackish marsh